Praktik Kepemimpinan Kolaboratif dalam Mewujudkan Hubungan Harmonis - Norhafizatur Rahmi; Noor Hidayah Safitri; Ade Rahma Al Khafi; Fitriah Fitriah; Adinda Maharani; Ziska Auliya Azizah; Suhaimi Suhaimi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Collaborative leadership is a leadership approach that emphasizes synergistic relationships between school principals and all educational skatehoders, including the community, parents, and teachers. This study aims to analyze collaborative leadership practices in fostering harmonious relationships between schools, families, and communiities. This research employs a qualitative approach using library research method through a Systematic Literature Review (SLR) design. Literature sources were obtained from academic databases, particularly Google Scholar, covering publication from 2020 to 2026, and manage using Mendeley reference softwere. The findings reveal that collaborative leadership plays a significant role in strengthening the tri-center education partnership through three main strategies: building open communication, forming collaborative work teams, and develeoping community partnership programs. Parental involvement proved to have a significant positive impact on student academic achievement, while community support enriches school educational resources. Furthermore, the implementation of collaborative leadership contributes to creating a more democratic work culture, enhancing teacher professionalism, and improving the overall quality of education. It is concluded that collaborative leadership is an effective approach for creating harmonious, inclusive, and suistainable educationl environments that support the holistic development of students.